IL-33trap-mediated IL-33 neutralization does not exacerbate choroidal neovascularization, but fails to protect against retinal degeneration in a dry age-related macular degeneration model. (June 2021) - Van Hove, Inge; Van Bergen, Tine; Etienne, Isabelle; Holgado, Aurora; Afonina, Inna S.; Beyaert, Rudi; Feyen, Jean HM.; Hu, Tjing-Tjing
Abstract: The progressive and sight-threatening disease, age-related macular degeneration (AMD), is a growing public health concern due to ageing demographics, with the highest unmet medical need for the advanced stage of dry AMD, geographic atrophy. The pathogenesis underlying AMD is driven by a complex interplay of genetic and environmental factors. There is ample evidence that inflammation is strongly involved in AMD development. Interleukin-33 (IL-33) has been proposed to be critically involved in retinal degeneration, but a protective role in eye pathophysiology was also demonstrated. The current study investigated the therapeutic potential of IL-33trap, a novel IL-33-neutralizing biologic, in dry AMD/geographic atrophy and, based on controversial data regarding the protective versus detrimental functions of IL-33 in neovascularization, evaluated the risk of progression to wet AMD by IL-33 neutralization. Repeated intravitreal (IVT) injections of IL-33trap in the mouse laser-induced choroidal neovascularization model did not exacerbate neovascularization or leakage, while it significantly inhibited inflammatory cell infiltration in the retinal pigment epithelium and choroid. On the contrary, IVT treatment with IL-33trap significantly induced retinal inflammation and could not prevent retinopathy induction in the mouse sodium iodate (NaIO3 ) model. Overall, these data suggest a complex and dichotomous role of IL-33 in eye pathology and indicate that IL-33 neutralization is not able to prevent onset and progression of dry AMD pathogenesis. Highlights: IL-33trap reduces inflammation during laser-induced choroidal neovascularization. Leakage and choroidal neovascularization are not affected by IL-33 neutralization. IL-33 neutralization induces an inflammatory response in a dry AMD mouse model. IL-33trap does not protect mice from sodium iodate-induced retinopathy.